A Review of Impact of Bam Earthquake on Cutaneous Leishmaniasis and Status: Epidemic of Old Foci, Emergence of New Foci and Changes in Features of the Disease - Mohammad Reza Aflatoonian; Iraj Sharifi; Bahnaz Aflatoonian; Mohammad Reza Shirzadi; Mohammad Mahdi Gouya; Alireza Kermanizadeh (Tehran University of Medical Sciences, 2016)
Background: Global findings indicate that incidence rate of cutaneous leishmaniasis (CL) has significantly increased during the past decade, as documented in many countries. This review was aimed to evaluate the trend of CL cases in terms of demographic and clinical characteristics during a decade after the earthquake (2003-2012) compared to the corresponding period before the earthquake in Bam (1993-2003). Methods: Direct smear preparations along with different intrinsic methods were used for detection and identification of the causative agents. Results: Overall, 20999 cases of CL have occurred during the last 20 years (1993-2012), 6731 cases before and 14268 cases after the earthquake (P< 0.001). Conclusions: Following a major earthquake, several risk factors could activate epidemics of cutaneous leishmaniasis in old foci and induce emerging foci in new areas.